Neonatal phencyclidine as a model of sex-biased schizophrenia symptomatology in adolescent mice. - Dutra-Tavares, Ana Carolina; Souza, Thainá P.; Silva, Juliana O.; Semeão, Keila A.; Mello, Felipe F.; Filgueiras, Claudio C.; Ribeiro-Carvalho, Anderson; Manhães, Alex C.; Abreu-Villaça, Yael (Psychopharmacology, 2023)
Sex-biased differences in schizophrenia are evident in several features of the disease, including symptomatology and response to pharmacological treatments. As a neurodevelopmental disorder, these differences might originate early in life and emerge later during adolescence. Considering that the disruption of the glutamatergic system during development is known to contribute to schizophrenia, we hypothesized that the neonatal phencyclidine model could induce sex-dependent behavioral and neurochemical changes associated with this disorder during adolescence. C57BL/6 mice received either saline or phencyclidine (5, 10, or 20 mg/kg) on postnatal days (PN) 7, 9, and 11. Behavioral assessment occurred in late adolescence (PN48-50), when mice were submitted to the open field, social interaction, and prepulse inhibition tests. Either olanzapine or saline was administered before each test. The NMDAR obligatory GluN1 subunit and the postsynaptic density protein 95 (PSD-95) were evaluated in the frontal cortex and hippocampus at early (PN30) and late (PN50) adolescence. Neonatal phencyclidine evoked dose-dependent deficits in all analyzed behaviors and males were more susceptible. Males also had reduced GluN1 expression in the frontal cortex at PN30. There were late-emergent effects at PN50. Cortical GluN1 was increased in both sexes, while phencyclidine increased cortical and decreased hippocampal PSD-95 in females. Olanzapine failed to mitigate most phencyclidine-evoked alterations. In some instances, this antipsychotic aggravated the deficits or potentiated subthreshold effects. These results lend support to the use of neonatal phencyclidine as a sex-biased neurodevelopmental preclinical model of schizophrenia. Olanzapine null effects and deleterious outcomes suggest that its use during adolescence should be further evaluated.